+0  
 
0
425
2
avatar+317 

It says 'simplify using power of laws.' I don't understand this question.

 

(3x2y3)(2xy2)2

------------------

      -2x2 y

 Jan 27, 2017
 #1
avatar+8943 
0

(3x2y3)(2xy2)2

------------------

      -2x2 y

 

\(\large \frac{(3x\times2y^3)(2x y^2 )^2}{-2x^2y}\)

 

\(=\large \frac{(3x\times2y^3)(4x^2 y^4 )}{-2x^2y}\) 

 

\(=-12xy^6\)

 

laugh  !

 Jan 27, 2017
 #2
avatar+20217 
0

I think 'Laws of powers' would be clearer....

 

 

(3x2y3)(2xy2)2

------------------         =    3x^2y^3 (4x^2y^4) / -2x^2y  = 12x^4y^7/(-2x^2y) = -6x^2y^6

      -2x2 y

 Jan 27, 2017

17 Online Users

avatar